PERANCANGAN APLIKASI PENGECEKAN DAN PEMESANAN LAPANGAN BASKET DI JAKARTA BERBASIS ANDROID - Juan Elber Kristian; Zyad Rusdi; Manatap Dolok Lauro (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Basketball is one of the most popular sports today. The community loves playing basketball, especially among youths.That is one of the reasons why basketball offers chances to operate a basketball court leasing company. One of the requirements for beginning a basketball court leasing company is the high level of community involvement.If the desired basketball court has already been ordered, the prospective tenant will need to find another court, according to observations made with basketball court providers and field users. Another issue is that it is still difficult for prospective basketball court users to learn about the courts that are currently available. The field supplier also has challenges; for instance, they continue to manually record orders. As a result, the best way to address the issues at hand is to develop information technology, such as an Android-based basketball court checking and booking application, which would make it simpler for potential tenants to make field reservations and access data about schedules, locations, and court prices.It is believed that the application will help field service providers and renters make the field order procedure very effective. This application's development makes use of the Android Studio program and the MySQL database.